Exploring the Pathways of Intelligent Media Technology Intervention in the Reform of Aesthetic Education in Higher Education - Dong, Guangchao; Hu, Lingling (Transactions on Economics, Business and Management Research, 2024)
The reform of aesthetic education in higher education institutions is urgently needed to adapt to contemporary educational concepts and development principles. Intelligent media technology, characterized by abundant information resources, strong timeliness, and high interactivity, offers new avenues for reforming aesthetic education in higher education. The current challenges faced by this reform include the neglect of aesthetic education, the low digital literacy of the teaching staff, and the potential risks associated with intelligent media technology. Therefore, guided by the principle of "student-centered education," this paper explores the pathways of integrating intelligent media into the reform of aesthetic education in higher education from four perspectives: enhancing the digital literacy of aesthetic education teachers and students; optimizing the top-level design of higher education institutions; integrating high-quality aesthetic education resources and building intelligent media platforms for aesthetic education; promoting diversified linkages to achieve organic integration; and strengthening network supervision to improve the aesthetic education support system.